Experimental aspects of partially premixed pulsating combustion - Ferreira, Daniel Silva [UNESP]; Lacava, Pedro Teixeira; Ferreira, Marco Aurélio; De Carvalho Jr., João Andrade [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 2005)
The pulsating combustion process has won interest in current research due to indications that its application in energy generation can offer several advantages, such as: fuel economy, reduced pollutants formation, increased rate of convective heat transfer and reduced investment, when compared with conventional techniques. An experimental study has been conducted with the objective of investigating the effects of combustion driven acoustic oscillations in the emission rates of combustion gases, especially carbon monoxide and nitrogen oxides. The experiments were conducted in a water-jacketed 1-m long by 25-cm internal diameter stainless steel vertical tube. The combustor operated with liquefied petroleum gas (LPG) in both oscillatory and non oscillatory conditions, under the same input conditions. Part of the reactant mixture was excited acoustically, before the burner exit, by a speaker positioned strategically. The burner was aligned with the chamber longitudinal axis and positioned at its bottom. The experiments were conducted for 0.16 g/s of LPG burning in stoichiometric equivalence ratio. The main conclusions were: a) the pulsating combustion process produces more uniform fuel/air profile than the non pulsating process, b) close to stoichiometric equivalence ratio the pulsating combustion process generates higher rates of NO x; c) the frequency has a strong influence in NO x emission, but the pressure amplitude has a weak influence; d) the presence of the acoustic field may change drastically the combustion gas emissions in diffusion flames, but in pre-mixed flames the influence is not as strong.
Keywords: Acoustic oscillations; Convective heat transfer; Emission rates; Energy generation; Longitudinal axis; Pulsating combustion process; Reduced pollutants formation; Stainless steel vertical tube; Acoustic fields; Carbon monoxide; Effluents; Fuel burners; Fuel economy; Heat transfer; Liquefied petroleum gas; Nitrogen oxides; Stainless steel; Stoichiometry; Combustion